2012
DOI: 10.1186/1471-2369-13-139
|View full text |Cite
|
Sign up to set email alerts
|

Renal arterial resistive index is associated with severe histological changes and poor renal outcome during chronic kidney disease

Abstract: BackgroundChronic kidney disease (CKD) is a growing public health problem and end stage renal disease (ESRD) represents a large human and economic burden. It is important to identify patients at high risk of ESRD. In order to determine whether renal Doppler resistive index (RI) may discriminate those patients, we analyzed whether RI was associated with identified prognosis factors of CKD, in particular histological findings, and with renal outcome.MethodsRI was measured in the 48 hours before renal biopsy in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 40 publications
(88 reference statements)
3
103
0
7
Order By: Relevance
“…were significantly higher than those of the patients in the remission and responded-residual hypertension groups ( Figure S1). Thus, high RI may indicate the presence of established renal parenchymal damage [9][10][11] or arteriosclerotic changes that would contribute to intractable or residual hypertension after adrenalectomy. Indeed, it was reported that in patients with untreated PA, the kidneys presented histopathologic changes, such as sclerosis of glomeruli, atrophy of the tubules, and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were significantly higher than those of the patients in the remission and responded-residual hypertension groups ( Figure S1). Thus, high RI may indicate the presence of established renal parenchymal damage [9][10][11] or arteriosclerotic changes that would contribute to intractable or residual hypertension after adrenalectomy. Indeed, it was reported that in patients with untreated PA, the kidneys presented histopathologic changes, such as sclerosis of glomeruli, atrophy of the tubules, and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Color Doppler ultrasonography was performed by 2 well-trained ultrasonographers who were not informed of the details of the study to avoid any potential bias. The tracing findings were examined by an experienced reader who was blinded to the patients' clinical information.…”
Section: Renal Doppler Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Esses índices comparam o fluxo durante a sístole e a diástole, sendo razões das velocidades obtidas do espectro Doppler. Por isso, ao contrário da análise isolada da velocidade, os índices têm como vantagem a independência da correção do ângulo, sendo usados para avaliação de vasos muito pequenos e tortuosos em que é difícil a correção do ângulo, como no caso das artérias intrarrenais (CARVALHO, 2009;BIGÉ et al, 2012).…”
Section: Ultrassonografia Em Modo Dopplerunclassified
“…However, although elevated RRI predicted adverse renal outcome in several cohort studies (10)(11)(12)(13)(14)(15)(16)(17)(18), these were mostly small-sized, and RRI was not compared against established models for CKD progression. Moreover, there is concern that RRI may not provide organ-specific information on structural or functional abnormalities within the kidneys, but rather reflects systemic vascular disease.…”
Section: Introductionmentioning
confidence: 99%